Remdesivir and Cyclosporine Synergistically Inhibit the Human Coronaviruses OC43 and SARS-CoV-2 - Hsu, Hsing-Yu; Yang, Cheng-Wei; Lee, Yue-Zhi; Lin, Yi-Ling; Chang, Sui-Yuan; Yang, Ruey-Bing; Liang, Jian-Jong; Chao, Tai-Ling; Liao, Chun-Che; Kao, Han-Chieh; Wu, Szu-Huei; Chang, Jang-Yang; et al. (Frontiers in Pharmacology, 2021)
Remdesivir, a prodrug targeting RNA-dependent-RNA-polymerase, and cyclosporine, a calcineurin inhibitor, individually exerted inhibitory activity against human coronavirus OC43 (HCoV-OC43) in HCT-8 and MRC-5 cells at EC50 values of 96 ± 34 ~ 85 ± 23 nM and 2920 ± 364 ~ 4419 ± 490 nM, respectively. When combined, these two drugs synergistically inhibited HCoV-OC43 in both HCT-8 and MRC-5 cells assayed by immunofluorescence (IFA). Remdesivir and cyclosporine also separately reduced IL-6 production induced by HCoV-OC43 in human lung fibroblasts MRC-5 cells with EC50 values of 224 ± 53 nM and 1292 ± 352 nM, respectively; and synergistically reduced it when combined. Similar trends were observed for SARS-CoV-2, which was (i) separately inhibited by remdesivir and cyclosporine with respective EC50 values of 3962 ± 303 nM and 7213 ±143 nM by IFA, and 291 ± 91 nM and 6767 ± 1827 nM by a plaque-formation assay; and (ii) synergistically inhibited by their combination, again by IFA and plaque-formation assay. Collectively, these results suggest that the combination of remdesivir and cyclosporine merits further study as a possible treatment for COVID-19 complexed with a cytokine storm.